2020
DOI: 10.1097/pgp.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Adenosarcoma Originating in Adenomyosis: Report of an Extremely Rare Phenomenon and Review of Published Literature

Abstract: Müllerian adenosarcoma is an uncommon biphasic malignant tumor most often occurring in the uterine corpus and derived from native surface endometrium. We report a case of intramural uterine adenosarcoma arising in association with adenomyosis, in the absence of tumor involving the surface endometrium. This is an extremely rare phenomenon, with only 8 other published cases of uterine corpus adenosarcoma in the absence of surface endometrial involvement, 5 originating in adenomyosis and 3 in adenomyomas. We revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Demarcated nodules were not observed on preoperative MRI or included in macroscopic findings of the resected uterus. Many cases of malignant tumors originating from adenomyosis exhibited demarcated lesions in the myometrium [ 6 , 7 , 15 , 17 , 20 ], and abnormal proliferation, as observed in our case, has not been reported to our knowledge. Moreover, the preoperative serum CA19-9 level in our case was markedly high at 115,950 U/mL.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Demarcated nodules were not observed on preoperative MRI or included in macroscopic findings of the resected uterus. Many cases of malignant tumors originating from adenomyosis exhibited demarcated lesions in the myometrium [ 6 , 7 , 15 , 17 , 20 ], and abnormal proliferation, as observed in our case, has not been reported to our knowledge. Moreover, the preoperative serum CA19-9 level in our case was markedly high at 115,950 U/mL.…”
Section: Discussioncontrasting
confidence: 43%
“…The most frequent histological subtype of malignant lesions is endometrioid carcinoma [ 3 ]. In our literature review, we found 23 well-documented cases of other histological subtypes as follows: 4 clear cell carcinomas [ 3 6 ], 4 serous carcinomas [ 4 , 7 , 8 ], 6 serous endometrial intraepithelial carcinomas [ 8 , 9 ], 6 adenosarcomas [ 10 – 15 ], and 1 case each of adenosquamous carcinoma [ 16 ], carcinosarcoma [ 17 ], and mucinous carcinoma (minimal deviation adenocarcinoma; MDA) [ 18 ]. Therefore, the current case is the second case of mucinous carcinoma originating from uterine adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the "unbiased study endpoints" domain, the risk of bias was low in 14 studies [13,14,17,18,20,24,[29][30][31][32][33]37,39,40,42], unclear in 11 studies [15,16,19,22,23,[26][27][28]34,35], and high in six studies [12,21,25,36,38,41]; in particular, in the studies at high risk of bias, Colman and Rosenthal's criteria were only partially fulfilled.…”
Section: Assessment Of Risk Of Bias Among Studiesmentioning
confidence: 98%
“…All included studies were case reports [36][37][38][39][40][41], except for four case series [12,34,35,42] (Table 1).…”
Section: Characteristics Of the Included Studies And Study Populationmentioning
confidence: 99%
See 1 more Smart Citation